The Theory of Harmony - Schoenberg, Arnold 1874-1951; Carter, Roy E. (London Faber and Faber, 1983)
This book will come as a joy, a revelation, a warm reassurance. From this one book one might well learn less about harmony than about form, about aesthetics, even about life. Some will accuse Schoenberg of not concentrating on the topic at hand, but such an accusation, though well-founded, would miss the point of Theory of Harmony, because the heart and soul of the book is to be found in his vivid and penetrating digressions. They are the fascinating reflections of a great and humane musician who was a born writer as well. - from the book.
Keywords: Music theory